Comparative Genomics of Monkeypox Virus Isolates from Sudan and Other Endemic Regions: Insights into Viral Evolution and Spread - Shina Abdulkadir (Scientific Journal of Dermatology and Venereology, 2023)
Introduction: Monkeypox, a zoonotic viral disease endemic to Central and West Africa, has recently gained global attention due to outbreaks beyond its traditional range. Understanding the genomic diversity of monkeypox virus (MPXV) isolates, particularly those from Sudan, is crucial for effective public health surveillance and vaccine development. Methods: In this study, we employed comparative genomics to analyze MPXV isolates from Sudan and other endemic regions. We utilized publicly available genomic sequences from NCBI's GenBank database. Phylogenetic analysis, sequence alignment, and identification of single nucleotide polymorphisms (SNPs) were performed to assess genetic diversity and identify potential geographic or temporal clustering. Results: Our analysis revealed distinct genetic lineages of MPXV circulating in Sudan compared to other endemic regions. Specific SNPs and genomic signatures were identified that could serve as potential markers for differentiating Sudanese isolates. Notably, some Sudanese isolates exhibited closer genetic relatedness to isolates from recent outbreaks outside of Africa, suggesting potential transmission pathways. Conclusion: This study provides valuable insights into the genomic diversity of MPXV in Sudan and other endemic regions. The identification of Sudan-specific genomic signatures highlights the importance of considering regional variations in public health surveillance and vaccine development efforts. Continued genomic surveillance is essential for monitoring the evolution of MPXV and detecting potential emerging variants with altered virulence or transmissibility.